Collinear deflection method for the measurement of thermal conductivity of transparent single layer anisotropic material - Kim, Moojoong; Park, Kuentae; Kim, Gwantaek; Yoo, Jaisuk; Kim, Dong Kwon; Kim, Hyunjung (Applied Sciences (Switzerland), 2019)
Transparent anisotropic materials have garnered attention along with the growth of the semiconductor and display industries. Transparent anisotropic materials have the characteristic of varying electrical, optical, and thermal properties based on their crystal orientation, and many studies are being conducted on this topic. In order to utilize transparent anisotropic materials properly, thermal properties such as thermal conductivity are essentially required. However, due to the limitations of the existing thermal property measurement methods for transparent anisotropic materials, it is difficult to provide the thermal properties of transparent anisotropic materials. To address this problem, a transparent anisotropic collinear method capable of measuring the effective thermal conductivity of a transparent anisotropic material according to its crystal orientation is proposed in this paper. To this end, the internal temperature distribution of a transparent anisotropic material and the phase delay of the probe beam were theoretically derived through a numerical analysis model that uses a three-dimensional heat conduction equation. This model was applied to anisotropic thermal conductivity with orthorhombic structure. To verify the proposed method of measuring the thermal conductivity of a transparent anisotropic material, the thermal properties of 3 mm-thick A-plane sapphire glass were measured and compared with those of the existing literature. It was confirmed that the absolute errors were less than about 4 W/mk.
Keywords: Anisotropic; Collinear; Photothermal; Thermal conductivity; Thermal properties